Development and emerging trends in gastrointestinal dysfunction of Parkinson’s disease: a decade-long bibliometric analysis - Sun, Yujia; Yang, Haoyu; Zhang, Junfeng; Cong, Shan; Wang, Lin; Yu, Tao (Frontiers in Aging Neuroscience, 2025)
Gastrointestinal (GI) dysfunction represents a prevalent non-motor symptom of Parkinson’s disease (PD) that not only contributes significantly to disease progression but also substantially compromises patients’ quality of life. Over the past decade, research in this domain has expanded considerably. To systematically delineate the knowledge framework and evolving trends, we performed a bibliometric analysis of publications on GI and PD from 2015 to 2025. A total of 924 articles were retrieved from the Web of Science Core Collection (WoSCC). Co-occurrence, clustering, and collaboration network analyses were performed using VOSviewer, CiteSpace, and the R package Bibliometrix. For findings validation, the PubMed database was incorporated as an independent external validation dataset, providing complementary verification of keyword analyses derived from WoSCC. Our analysis revealed a steady annual increase in publication output. China and the United States emerged as the most prolific contributors globally, with the latter attaining the highest total citation count. At the institutional level, Capital Medical University led in publication output, whereas the University of Helsinki ranked highest in both total and average citations. Among journals, Parkinsonism & Related Disorders published the most papers on this topic, while Movement Disorders received the most citations. Keyword cluster analyses identified three primary research frontiers: (1) pathogenesis, focusing on α-synuclein (α-syn), the brain-gut-microbiome axis, and the enteric nervous system; (2) clinical manifestations, especially dysphagia and constipation; and (3) therapeutic interventions, particularly fecal microbiota transplantation and probiotics. By integrating established knowledge and highlighting emerging trends, this review aims to inform and guide future research and clinical practice in the field of gastrointestinal dysfunction in PD.